Hubungan Asupan Zat Gizi Makro Dan Aktivitas Fisik Dengan Rasio Lingkar Pinggang Pinggul Pasien Jantung Koroner Rawat Jalan Di RSUD Dr. Moewardi Surakarta - Ningsih, Ratna, Dwi Sarbini, S.ST., M.Kes, Muwakhidah, SKM, M.Kes (2015)
Background: Coronary heart disease is one of killing disease especially in Indonesia. One of the factors that cause coronary heart disease is macro-nutrient intake and low physical activity. The risk factor of coronary heart disease can be detected by measuring the ratio of waist-to-hip circumference (waist hip ratio). Objective: The aim of this study was to determine the relationship of macro nutrient intake and physical activity with waist hip ratio of coronary heart outpatients at RSUD Dr. Moewardi Surakarta. Methods: Descriptive analytic research namely cross sectional method was used in this study. The number of subject that used in this study was 30 coronary heart outpatients in RSUD Dr. Moewardi Surakarta. Measurements of macro nutrient intake using Food Frequency Questionnaire, Physical activity data collection using 24-hour recall for 1 week, and waist hip ratio using metlin. Data analysis was performed by the statistical test Pearson Correlation. Result: The results showed the majority of protein intake is more (91,7%), fat intake is more (93,3%), carbohydrate intake is more (96%) and physical activity is lightweight (100%). Waist hip ratio of coronary heart disease patients who have a risk are 29 patients and 1 patient did not have a risk suffer from coronary heart disease. Conclusion: conclusions of this study is there is a relationship of macro nutrient intake and physical activity with the waist hip ratio of coronary heart outpatients at RSUD Dr. Moewardi Surakarta.